Incidencia del embarazo adolescente en la salud mental de una adolescente de 15 años de la ciudad de Babahoyo - Chávez Palma, Nohelia Melissa (2023)
This document describes the study on “the incidence of pregnancy on the mental health of a 15-year-old adolescent from the city of Babahoyo” which was addressed with the line of research of the career called “Clinical and Forensic” and is related to the subline in “Individual and/or group psychotherapies”. The main objective in the case was to identify the incidence on the dependent and independent variables and as specific objectives: determine psychological signs and symptoms, establish a psychotherapeutic model and promote the learning of psychological tools for the development of skills that allow mitigating the discomfort of the symptomatology. To detect this phenomenon, data were collected through psychological techniques and instruments such as: observation, interviews, clinical history, psychometric tests such as the FF-SIL and DASS. With the support of these methods, it was possible to conclude that, if there is an impact on the variables, therefore, the clinical manifestations of this case were related to the symptoms detailed in the ICD-10 and an “Adjustment Disorder” was diagnosed. For this reason, a psychotherapeutic approach was used based on the Cognitive Behavioral Therapy model, which is a model that addresses this disorder with a holistic and biopsychosocial perspective. It focuses on reactivating the individual and providing them with the tools so that they can begin to see their life from another point of view. With this approach, positive results were optimized and symptoms decreased. To conclude, I need to mention that the study was possible due to the patient's predisposition and commitment throughout the psychotherapeutic process.